Desarrollo de ambientes de aprendizaje inmersivos mediante realidad aumentada utilizando marcadores para la enseñanza-aprendizaje de estudiantes de primero BGU. - Parco Macías, Anthony Alexander (2023)
This study aims to develop immersive learning environments through marker-based augmented reality for teaching-learning in first-year BGU students in the subject of Language and Literature. The lack of knowledge of educators with the management of computer resources and devices has meant that education needs to be innovated. Therefore, this proposal is made to innovate traditional teaching in the classroom. A type of applied research is used with a technological research design with an exploratory scope. The techniques for elaborating projects are used, such as Observation and Bibliographic Review. Additionally, the questionnaire was used as an instrument to measure acceptance, and the survey for data collection was used as a technique. A position control system for the Merge cube controlled by a joystick is developed. Therefore, immersive learning environments are created within the CoSpaces EDU application from the Language and Literature book of the first BGU editorial SM, with the purpose of that teachers and students apply the laboratory with augmented reality, practical teaching, and learning guides are developed to measure the acceptance of augmented reality environments, a survey was carried out on a student sector of 22 first-year BGU students from the U. E "La Inmaculada" in the city of Ambato. The results obtained in the investigation are a model for the operation of immersive environments, five teaching guides, and five learning guides.